Analysis of Criminal Sentences Against Perpetrators of Criminal Acts of Theft with Aggravating Criminal Case Study Decision Number: 208/Pid.B/2024/PN Jap - Alfarizi Lubis, Muhammad Fathur; Mashdurohatun, Anis (UNISSULA Semarang, 2025)
The crime of theft is one form of crime that often occurs in society and has a significant impact, both for victims and perpetrators. In the context of law, theft is not only seen from the aspect of its criminality, but also from the broader perspective of justice. In Indonesia, Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that